Factors Affecting the Serum Cotinine Level of Male Smokers in Malang, Indonesia - Kumboyono Kumboyono; Indah Nur Chomsy; Wahyu Santoso Hidayat; Wahyu Santoso Hidayat; Ardhi Khoirul Hakim; Nadya Neyza Shalshabilla; Hidayat Sujuti; Cholid Tri Tjahtjono; Arie Srihardyastutie; Tita Hariyanti; Titin Andri Wihastuti (International Journal of Medical Toxicology and Forensic Medicine, 2023)
Background: In tobacco, nicotine is the primary toxic agent that causes health problems. As a primary metabolite of nicotine, cotinine is frequently used as an accurate measure of exposure to tobacco smoke. This study aims to find the factors affecting the serum cotinine level of male smokers in Malang, Indonesia. Methods: This cross-sectional study was conducted on 183 men who smoke regularly in Malang, Indonesia. They were selected by a purposive sampling method. Nicotine dependency and cotinine level were measured using the Fagerstrom test for nicotine dependence and the human cotinine ELISA Kit, respectively. Multiple linear regression analysis was performed to determine the effect of age, smoking duration, cigarette type, and the nicotine dependence on the continue level. ANOVA and independent t-test were also used for testing the study hypothesis. The significance level was set at 0.05. Results: Based on the ANOVA results, the factors of age, smoking duration, type of cigarette, and nicotine dependence together had a significant effect on the cotinine level (P<0.001). Based on the independent t-test results, only the age factor had a significant effect on the cotinine level (P<0.001). Conclusion: Older male smokers may have higher cotinine level. Other factors including duration of smoking, type of cigarette, and nicotine dependence have no significant effect on cotinine level of male smokers.